Thinking through Confucius - Hall, David L. (SUNY series in systematic philosophy., 1987)
Thinking Through Confucius critically interprets the conceptual structure underlying Confucius' philosophical reflections. It also investigates "thinking," or "philosophy" from the perspective of Confucius. That authors suggest that an examination of Chinese philosophy may provide an alternative definition of philosophy that can be used to address some of the pressing issues of the Western cultural tradition.